Asthma phenotypes, associated comorbidities, and long‐term symptoms in COVID‐19. Issue 1 (19th June 2021) - Eggert, Lauren E.; He, Ziyuan; Collins, William; Lee, Alexandra S.; Dhondalay, Gopal; Jiang, Shirley Y.; Fitzpatrick, Jessica; Snow, Theo T.; Pinsky, Benjamin A.; Artandi, Maja; Barman, Linda; Puri, Rajan; et al.
Abstract: Background: It is unclear whether asthma and its allergic phenotype are risk factors for hospitalization or severe disease from SARS‐CoV‐2. Methods: All patients over 28 days old testing positive for SARS‐CoV‐2 between March 1 and September 30, 2020, were retrospectively identified and characterized through electronic analysis at Stanford. A sub‐cohort was followed prospectively to evaluate long‐term COVID‐19 symptoms. Results: 168, 190 patients underwent SARS‐CoV‐2 testing, and 6, 976 (4.15%) tested positive. In a multivariate analysis, asthma was not an independent risk factor for hospitalization (OR 1.12 [95% CI 0.86, 1.45], p = .40). Among SARS‐CoV‐2‐positive asthmatics, allergic asthma lowered the risk of hospitalization and had a protective effect compared with non‐allergic asthma (OR 0.52 [0.28, 0.91], p = .026); there was no association between baseline medication use as characterized by GINA and hospitalization risk. Patients with severe COVID‐19 disease had lower eosinophil levels during hospitalization compared with patients with mild or asymptomatic disease, independent of asthma status ( p = .0014). In a patient sub‐cohort followed longitudinally, asthmatics and non‐asthmatics had similar time to resolution of COVID‐19 symptoms, particularly lower respiratory symptoms. Conclusions: Asthma is not a risk factor for more severe COVID‐19 disease. Allergic asthmatics were half as likely to be hospitalized with COVID‐19 compared with non‐allergic asthmatics. Lower levels of eosinophil counts (allergic biomarkers) were associated with a more severe COVID‐19 disease trajectory. Recovery was similar among asthmatics and non‐asthmatics with over 50% of patients reporting ongoing lower respiratory symptoms 3 months post‐infection. Abstract : Asthma is not a risk factor for more severe COVID‐19 disease. Allergic asthmatics are half as likely to be hospitalized compared with non‐allergic asthmatics and lower levels of eosinophil counts (allergic biomarkers) are associated with a more severe COVID‐19 disease trajectory. Recovery is similar among asthmatics and non‐asthmatics. Abbreviation: COVID, coronavirus disease 2019.